Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1007/bf00226045
|View full text |Cite
|
Sign up to set email alerts
|

Degenerated boutons in the fundus striati (nucleus accumbens septi) after lesion of the parafascicular nucleus in the cat

Abstract: An attempt has been made to reveal which of the nine different types of synapses in the fundus striati, discriminated in a previous study, degenerate following experimental lesions in the parafasciculo-center median complex of the cat. Two types of synaptic contacts were found to be degenerated two days after the lesion was performed: (1) the axo-spinous type IV, characterized by densely-packed, small, round vesicles and a strong asymmetric thickening, and (2) the axo-dendritic or axo-somatic type VII, again c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1977
1977
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…9 appears similar to the type IV boutons of Hassler et al (7). They considered that this type is a bouton from the centro-median-parafascicular complex off the thalamus, which is suggested to be cholinergic (41) and to terminate on spines of a medium-sized neuron (28,30) (type I ChAc positive neuron in the present study).…”
Section: Resultssupporting
confidence: 85%
“…9 appears similar to the type IV boutons of Hassler et al (7). They considered that this type is a bouton from the centro-median-parafascicular complex off the thalamus, which is suggested to be cholinergic (41) and to terminate on spines of a medium-sized neuron (28,30) (type I ChAc positive neuron in the present study).…”
Section: Resultssupporting
confidence: 85%
“…Cortical terminals form asymmetric synapses primarily with dendritic spines of the medium-sized densely spiny projection neurons (Kemp & Powell, 1971a, b, c, d;Bak et al, 1975;Hassler et al, 1978;Somogyi et al, 1981;Smith & Bolam, 1990;Smith et al, 1998), and also with the dendrites of interneurons (Bolam & Bennett, 1995). Chung et al (1976Chung et al ( , 1977 and Dube et al (1988) found thalamostriatal boutons establishing asymmetrical synapses on dendritic spines.…”
Section: Introductionmentioning
confidence: 98%